The Influence of Non-Specialist Teacher Competence on the Success of Arabic Language Learning at MI Nurul Huda Karangtalok Pemalang - Atiul Fana; Taufiqur Rohman (MASI Mandiri Edukasi, 2026)
This study aims to analyze the effect of non-specialist teacher competence on the success of Arabic language learning at MI Nurul Huda Karangtalok, Pemalang. The research employed a quantitative approach using an explanatory research design with a correlational method. The population consisted of 60 students, all of whom were selected as the research sample using a saturated sampling technique. Data were collected using a closed-ended questionnaire based on a five-point Likert scale to measure non-specialist teacher competence and learning success. The data were analyzed using validity and reliability tests, normality tests, simple linear regression, t-tests, and coefficient of determination analysis. The results revealed that non-specialist teacher competence had a positive and significant effect on the success of Arabic language learning, with a significance value of 0.000 (<0.05). The coefficient of determination (R²) was 0.360, indicating that teacher competence accounted for 36.0% of learning success. These findings suggest that non-specialist teacher competence plays an important role in improving Arabic language learning success at the Madrasah Ibtidaiyah level.